2012
DOI: 10.1007/s10611-011-9351-0
|View full text |Cite
|
Sign up to set email alerts
|

Promoting financial inclusion for effective anti-money laundering and counter financing of terrorism (AML/CFT)

Abstract: "Financial inclusion" is the delivery of financial services at affordable costs, especially to the disadvantaged and low income populations. Financial inclusion has gained some importance in the last few decades as a result of findings on the impact of "financial exclusion" on development and especially its correlation to poverty.This paper arguesthat access to financial services contributes to human and economic development; and that financial inclusion and effective AML/CFT are complementary to ensure the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…The relevant leading drivers for de-risking are the high cost of compliance with the CTF/AML regime based on risk-based approach, the high level of financial penalties, and the cost of the implementation of the sanctions regime (FATF, 2016). The fourth stage is financial exclusion; the generation of financial exclusion, including limited access to formal financial systems, has been a criticism of the AML/CTF regime (Shehu, 2012).…”
Section: Internal Exclusionary: Financial Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The relevant leading drivers for de-risking are the high cost of compliance with the CTF/AML regime based on risk-based approach, the high level of financial penalties, and the cost of the implementation of the sanctions regime (FATF, 2016). The fourth stage is financial exclusion; the generation of financial exclusion, including limited access to formal financial systems, has been a criticism of the AML/CTF regime (Shehu, 2012).…”
Section: Internal Exclusionary: Financial Culturementioning
confidence: 99%
“…in that 'what works in one jurisdiction may not necessarily work in another' (Shehu, 2012). In fact, there is a negative correlation between financial exclusion and using informal financial system.…”
Section: The Impact Of Financial Exclusionmentioning
confidence: 99%
“…In addition, the direct benefit transfer would enhance the security of payments and lower the associated crime incidents (Mundial, 2014). Shehu (2012) have observed that the promotion of financial inclusion would be an effective strategy against anti-money laundering and counter financing of terrorism.…”
Section: Benefits At Macro Economicmentioning
confidence: 99%
“…The demand for information about a customer becomes a problem, however, when the transaction request is made of a person without the necessary identity documents, while the expectation for data collection and recording by informal businesses is similarly problematic. In particular, this situation is a challenge for regulating migrant remittances, which in the past was largely via informal methods, and a challenge for efforts to promote financial inclusion when the persons currently “unbanked” are also “undocumented” (Shehu ). These two issues are outlined in the next two subsections, followed by a subsection presenting a case that has been made for the beneficial use of AML surveillance and laws for investigations of bribery and corruption by government officials.…”
Section: Consequences In Developing Statesmentioning
confidence: 99%
“…Meanwhile in the developing economy, the excluded may consist of a larger segment of the population that includes people who did not previously need an identity document, those working in the informal economy, and those living in unofficial and informal residences. The objective behind financial inclusion, on the other hand, is to counter these effects and to promote access and use of financial services (Shehu :308). A bank account is understood generally to provide a safer means to save money than an envelope under the mattress and access to more secure ways of transferring money than handing cash to an acquaintance to deliver to a family member back home.…”
Section: Consequences In Developing Statesmentioning
confidence: 99%